The complete plastid genome of Ruppia brevipedunculata Shuo Yu & den Hartog - Yu, Shuo (Mitochondrial DNA B Resour, 2020)
The taxonomy of Ruppia has long been confused due to its high plasticity in morphology. In this study, the complete plastid genome sequence of Ruppia brevipedunculata was successfully sequenced by the technology of Illumina. The whole plastid genome length was 158,943 bp and contained a typical quadripartite structure including one large single copy (LSC) region (88,857 bp), one small single copy (SSC) region (19,130bp) and a pair of inverted repeats (IR) regions (25,478bp). The GC content of this genome was 35.8%. The whole genome contained 132 genes including 87 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The phylogenetic analysis indicated that R. brevipedunculata and R. sinensis formed a distinct clade separated from Potamogeton perfoliatus.